The Belgian “plant-hunters” during the reign of Leopold I (1831-1870): success and paradox - Diagre, Denis (Circumscribere International Journal for the History of Science, 2011)
Although Belgium became a dominant nation in the area of horticulture in the 19th century, the history of its naturalists-collectors still awaits the global and thorough reflection that has been made in other countries (particularly, France and Germany). Given the current state of things, the author was able to highlight the existence of a “Belgian paradox” where the success of the national horticulture project – largely due to its collectors of plants - contrasts particularly with the little interest of Belgian scientific botany in tropical taxonomy and flowers. This article discusses several of the major causes, according to the author, of this odd phenomenon. Moreover, it argues for a comparative approach to the “motion to collect” in the 19th century involving historians of several European countries and originated in the countries where “plant hunters” were active. Besides its contribution to knowledge in history of science, this demarche supplies a treasure of facts useful for taxonomists interested in information on the herbalists they study and that serve as documental source for the study of biodiversity.